The Automatic Pest Trap (Rat) - Mohamad, Shahrul Nizam; Chew Chang Choon, (Evolution in Electrical and Electronic Engineering, 2023)
Plants, food, and health are important in human life. One of the direct effects caused by insects is the transmission of various illnesses to healthy plants, known as the pest-disease link. When the population of these pests grows and is not prevented, it will affect crop yields, health, and food supply. One of the main objectives of this project is to design an automatic pest trap so that it can be easily used to catch small pests, especially mice. This project is equipped with several electronic components such as infrared sensors to allow the door to be closed and opened. The use of this smart sensor is to detect pests and trap them effectively. This project can also use a power bank as a backup supply to allow all the components in the trap to work properly. The optimized design has been evaluated by varying two Infrared sensors as the main component in controlling the servo motor as a door to open and close when detecting pest movement. Apart from that, this project has also been equipped with Blynk IoT as an application to send notifications to users when there are pests that have been caught. Initially, the automatic pest trap design procedure including part drawing, material and condition settings, and property settings are all explained. then it is tested and recorded when the trap can detect movement to close and open the door effectively. It is concluded that the trained model can perform relatively well in classifying automatic pest traps. In the future, more data can be used in the training to increase and improve the accuracy and capability of this model.  So, the project was created as an attempt to overthrow the population of pests such as mice or any small pest so that the problems of crops, health, and food supply can be overcome. This trap also is simple to use, economical, safer for people, and easy to use to catch pests. In the future, the recommendation for this study is to improve the design such as the prototype design. Improving prototype design gives the project a better product in terms of durability, quality, and sustainability.